Analysis of Raw Materials Inventory Control Using Economic Order Quantity (EOQ) (Case Study of Synthetic Leather Raw Materials at Borselly) - Sinta Sri Nurjanah; Suci Putri Lestari; Barin Barlian (Penerbit Jurnal Indonesia, 2023)
The purpose of this study was to find out how the implementation of synthetic leather raw material inventory control has been carried out by Borselly, whether applying the EOQ method in controlling raw material inventory at Borselly is more optimal than without using the EOQ method. The method used in this research is a descriptive method with a quantitative approach with technical data collection through interviews, observation, literature study, and documentation. The data analysis tool used in this study is by using the Economic Order Quantity (EOQ) such as purchase frequency, safety stock, reorder point (ROP), and total inventory cost (TIC). Based on the research results, it is known that applying the EOQ method calculation has an effect on the company being better, the company can also make inventory costs more efficient and optimize inventory compared to policies using conventional methods